Assessment of Dapagliflozin by Using HPLC- Method Development, Validation and Stability Indicating Studies - Sanker Reddy, L. Siva; Nageswara Rao, R.; Raghavendra, K; Jayavarapu, Kumar Raja; Indumathi, B.; Gopal, N. Madan; Muneer, S.; Ushasree, B.; Prasad, L.A. Rama; Ayyappa G, Sampath (Journal of Neonatal Surgery, 2025)
This project's main objective is to develop and validate an RP-HPLC technique for dapagliflozin, an anti-diabetic medication that reversibly inhibits the human Sodium-Glucose Co-Transporter (SGLT2). The method should be easy to use, precise, and accurate. Methanol, ethanol, and isopropyl alcohol are among the organic solvents that dissolve it effectively. A p-value of 12.6 is provided. This experiment made use of the Column-C18 (5μm; 4.6×250mm). Acetonitrile and 1% IPA were combined in an 80:20 (v/v) ratio to create the selected mobile phase. 10 µg/ml was the injection volume, and 1.0 ml/min was the flow rate. A duration of retention of 2.9 minutes at 30°C was measured at 224 nm. With a r2 value of 0.9995, the range of linearity was found to be 5-100 µg/ml. A range of 98-102% was seen for the recovery. The respective limits of detection were 0.62 εg/ml and 0.2 εg/ml. The stress test results demonstrate that even in the presence of degradants, the method was still able to identify the medication.